Institutions, board structure, and corporate performance: Evidence from Chinese firms - Chen, Tao (Journal of Corporate Finance, 2015)
This paper investigates how institutional environment like property rights protection influences the size and composition of corporate boards, and further, how board structure impacts firm performance in China. Using a World Bank survey of 2400 public and private firms across 18 Chinese cities, I find robust evidence that weaker helping hand from the government is associated with a higher number and proportion of outsiders on the board, after controlling for the effects of firm complexity, growth opportunities, CEO characteristics, ownership, and the potential endogeneity concern. Furthermore, the results show that when firms are operating in a weak property rights environment, more outsiders improve corporate performance.